2012
DOI: 10.1364/oe.20.00b104
|View full text |Cite
|
Sign up to set email alerts
|

Linewidth-narrowing and intensity noise reduction of the 2nd order Stokes component of a low threshold Brillouin laser made of Ge_10As_22Se_68 chalcogenide fiber

Abstract: A compact second-order Stokes Brillouin fiber laser made of microstructured chalcogenide fiber is reported for the first time. This laser required very low pump power for Stokes conversion: 6 mW for first order lasing and only 30 mW for second order lasing with nonresonant pumping. We also show linewidth-narrowing as well as intensity noise reduction for both the 1 st and 2 nd order Stokes component when compared to that of the pump source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Only the Brillouin thresholds are significantly different. Indeed, the Brillouin threshold reach 85 mW in a 4·9 m-long SIF [35], while a threshold of only 6 mW were observed in only 3-m long MOF [36] (In that study the fiber design was close to the design illustrated in Figure 3(c)). The single-frequency Brillouin laser made with this fiber showed a promising frequency noise reduction of nearly 6 dB, as compared to the noise of the pump laser.…”
Section: In the Mid-infrared Regionmentioning
confidence: 69%
See 2 more Smart Citations
“…Only the Brillouin thresholds are significantly different. Indeed, the Brillouin threshold reach 85 mW in a 4·9 m-long SIF [35], while a threshold of only 6 mW were observed in only 3-m long MOF [36] (In that study the fiber design was close to the design illustrated in Figure 3(c)). The single-frequency Brillouin laser made with this fiber showed a promising frequency noise reduction of nearly 6 dB, as compared to the noise of the pump laser.…”
Section: In the Mid-infrared Regionmentioning
confidence: 69%
“…composition-dependent, with values of 8·2 GHz in a sulfur fiber [28] and 7·95 GHz in As-Se fibers (SIF or MOF) [35,36].…”
Section: Fiber Designs For Enhancing the Non-linear Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In both fiber 15,16 and waveguide 18 experiments, the configuration of the laser cavity imposed restrictions on the amount of power that could be coupled out of the cavity for detection. The output coupler with a larger fraction would introduce an extra loss per round trip and lead to an increase in the lasing threshold.…”
Section: Ring-cavity Lasermentioning
confidence: 99%
“…One possible way to build such a laser is to exploit the intrinsically narrow linewidth and tunability of stimulated Brillouin scattering (SBS). Recent studies have demonstrated that Brillouin lasers (BLs) can have orders of magnitude higher coherence than their pump sources [4][5][6][7]. The phase noise of the pump is transferred to the Stokes wave, but with significantly reduced magnitude due to the combined action of acoustic damping and cavity feedback [4].…”
mentioning
confidence: 99%